1988
DOI: 10.1002/lsm.1900080603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blood flow on laser probe temperature in human arteries

Abstract: Laser recanalization using metal capped fibers occurs by thermal vaporization of occluding plaque. However, little is known about the effects of blood and flow on the temperature of the laser probe or the arterial wall during lasing. To study this, probe and arterial wall temperatures were measured while a metal capped fiber, activated by an argon laser, was held stationary in a stenotic human peripheral artery. Arteries were perfused with saline and blood, and flow was varied from 0 to 140 cc/min. Probe tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This tended to slow the rate of rise (and fall) in temperature and while the peak temperatures were higher the clotkhar prevented dissipation of heat to the surroundings. Using aluminum-capped fibres (temperatures in air are only 50% of the Trimedyne probes used here), Silverman et al found that adventitial temperatures in vitro were similar when lasing in blood or saline despite the higher probe temperature in blood [17]. In vivo the blood medium might initially raise tip temperatures and enhance ablation until the development of a coagulum insulates it and then retards further ablation.…”
Section: Discussionmentioning
confidence: 94%
“…This tended to slow the rate of rise (and fall) in temperature and while the peak temperatures were higher the clotkhar prevented dissipation of heat to the surroundings. Using aluminum-capped fibres (temperatures in air are only 50% of the Trimedyne probes used here), Silverman et al found that adventitial temperatures in vitro were similar when lasing in blood or saline despite the higher probe temperature in blood [17]. In vivo the blood medium might initially raise tip temperatures and enhance ablation until the development of a coagulum insulates it and then retards further ablation.…”
Section: Discussionmentioning
confidence: 94%
“…SILVERMAN et al (92) confirmed that probe temperature is significantly higher in blood than in saline. The saline may act as a heat sink, potentially reducing the effect of the thermal probe by reducing its temperature.…”
Section: Efforts Towards More Efficient Ptlamentioning
confidence: 96%
“…Although the usage of shorter wave length, high energy and high frequency pulses of argon laser irradiation are now encouraged in PTLA (84,86,92,93), several studies with a continuous wave of argon laser irradiation during the PTLA procedures have been reported. STRIKWERDA et al (98) found that a short emission time and high-power exposures of continuous argon ion laser light result in the most rapid and efficient removal of atherosclerotic plaque.…”
Section: Laser Sourcesmentioning
confidence: 99%
“…Although the usage of shorter wave length, high energy and high frequency pulses of argon laser irradiation are now encouraged in PTLA (84,86,92,93), several studies with a continuous wave of argon laser irradiation during the PTLA procedures have been reported. STRIKWERDA et al (98) found that a short emission time and high-power exposures of continuous argon ion laser light result in the most rapid and efficient removal of atherosclerotic plaque.…”
Section: Laser Sourcesmentioning
confidence: 99%